2006
DOI: 10.1021/ja055782g
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Quenching Species in Ruthenium Tris-Bipyridine Electroluminescent Devices

Abstract: We have used matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry and micro-Raman spectroscopy to identify a quenching species that is formed during operation of [Ru(bpy)3]2+ electroluminescent devices. We identify this performance-degrading product to be the oxo-bridged dimer [(bpy)2(H2O)RuORu(OH2)(bpy)2]4+ and show this dimer to be an effective quencher of device luminescence. This work is the first to detect a specific chemical degradation product formed during iTMC OLED … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 21 publications
1
98
0
Order By: Relevance
“…This circumvents the steps of removing the capping electrode from the organic device and the additional solving procedure needed to transfer the material of interest in the analyzer. [11,12,17] To analyze the device of interest it is necessary to contact it to the ground potential of the (MA)LDI system. As sketched in Scheme 1, the samples can be contacted easily at their indium tin oxide (ITO) anodes.…”
Section: Collecting Spectra Through the Metal Cathodementioning
confidence: 99%
See 1 more Smart Citation
“…This circumvents the steps of removing the capping electrode from the organic device and the additional solving procedure needed to transfer the material of interest in the analyzer. [11,12,17] To analyze the device of interest it is necessary to contact it to the ground potential of the (MA)LDI system. As sketched in Scheme 1, the samples can be contacted easily at their indium tin oxide (ITO) anodes.…”
Section: Collecting Spectra Through the Metal Cathodementioning
confidence: 99%
“…[10] However, most of the chemical-analysis work done so far, in particular regarding degradation processes, has been done by dissolving the organic devices and analysing the solutions by different techniques like high-performance liquid chromatography (HPLC), [11] nuclear magnetic resonance (NMR) spectroscopy, [11] or matrixassisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS). [12] In particular MALDI-TOF-MS has become established for the detailed analysis of polymeric chains and proteins. [13,14] In this paper, we demonstrate the use of laser desorption/ ionization time-of-flight mass spectrometry (LDI-TOF-MS) as a powerful analysis technique for organic semiconductor devices.…”
Section: Introductionmentioning
confidence: 99%
“…[14] The origin of the low lifetimes of iTMC-based electroluminescent devices has been studied in detail only for devices using [Ru(bpy) 3 ] 2þ (bpy ¼ 2,2 0 -bipyridine) as the active component. [15,16] The intrinsic instability of the iTMC under working conditions was identified as the primary and predominant reason for device degradation. Moreover, these studies revealed that the instability of the iTMC complex leads with participation of water molecules to the generation of degradation products that act as efficient luminescence quenchers.…”
mentioning
confidence: 99%
“…complexes, which accounts for the efficient nonradiative quenching resulting from these states [40]. In addition, work on ruthenium(II) complexes has suggested that this bond lengthening/breaking process within the 3 MC state introduces a free coordination site that allows small molecules such as water to coordinate to the metal, quenching the emission and leading to degradation products within the device [13,41]. Thus, devices employing complexes with a small 3 MC-T 1 energy gap tend to not be stable unlike the case with 1 where the device stability is enhanced.…”
Section: Devicesmentioning
confidence: 99%